Performance Analysis of SATPOL PP to PPKM Policy in Administrative City of South Jakarta - Panjaitan, Kardo; Islah, Khikmatul (Jurnal Magister Administrasi Publik, 2021)
The policy of implementing restrictions on community activities (PPKM) is a policy made by the government in controlling the COVID-19 pandemic in Indonesia, so good performance is needed in guarding the policy. This study aims to describe the performance of the Civil Service Police Unit, South Jakarta Administration. Determination of informants using a purposive sampling technique. Data was collected by using interviews, observation, and documentation techniques. The validity of the data in this study uses data triangulation. Data analysis through the process of data collection, data presentation, conclusion drawing, and data verification. The data analysis technique used descriptive and qualitative analysis techniques. The results of the research on the performance of the Satpol PP in guarding the implementation of PPKM in the South Jakarta Administrative City are quite good in terms of several dimensions, namely the dimensions of work quality, dimensions of work quantity, dimensions of employee consistency, dimensions of cooperation and dimensions of employee attitudes, but still need improvement in the quality of work and consistency. The obstacles that affect the performance of the Civil Service Police Unit in overseeing the implementation of restrictions on community activities (PPKM) in the South Jakarta Administrative City are the lack of Civil Servant Investigators (PPNS), PPKM policies that are always changing, and the lack of public awareness of the importance of health protocols.